2010
DOI: 10.1002/prot.22729
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic repulsion between HIV-1 capsid proteins modulates hexamer plasticity and in vitro assembly

Abstract: Capsid protein (CA) is the major component of the human immunodeficiency virus type 1 (HIV-1) core. Three major phosphorylation sites have been identified at positions S(109), S(149) and S(178) in the amino-acid sequence of CA. Here, we investigated the possible consequences of phosphorylation at these sites on the CA hexamer organization and plasticity using in silico approaches. The biological relevance of molecular modeling was then evaluated by analyzing the in vitro assembly properties of bacterially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…To determine whether the viral core interacts with MELK, we purified One-STrEP-FLAG-(OSF)-tagged MELK protein expressed in HeLa cells, and viral cores from cell-free virions. The HIV-1 envelope was removed from virions and envelope-stripped cores were enriched by ultracentrifugation through a discontinuous 10% and 30% sucrose gradient with 0.1% Triton X-100 in the 10% sucrose layer, as previously reported [20] (Fig 2D). The envelope-stripped cores were characterized by transmission electron microscopy (TEM) showing recognizable ~100 nm cone-shaped structures similar to authentic HIV-1 cores (Fig 2E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether the viral core interacts with MELK, we purified One-STrEP-FLAG-(OSF)-tagged MELK protein expressed in HeLa cells, and viral cores from cell-free virions. The HIV-1 envelope was removed from virions and envelope-stripped cores were enriched by ultracentrifugation through a discontinuous 10% and 30% sucrose gradient with 0.1% Triton X-100 in the 10% sucrose layer, as previously reported [20] (Fig 2D). The envelope-stripped cores were characterized by transmission electron microscopy (TEM) showing recognizable ~100 nm cone-shaped structures similar to authentic HIV-1 cores (Fig 2E).…”
Section: Resultsmentioning
confidence: 99%
“…Envelope-stripped HIV-1 cores were prepared as described previously [20]. Briefly, HIV-1-containing culture supernatants were prepared by transiently transfecting HeLa cells with pNL4-3 using LipofectAMINE LTX PLUS (Invitrogen Corp., Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…However, in the latter case assembly typically requires relatively high protein concentrations and very high ionic strength (51,52,54) that may screen electrostatic repulsions in CA (63)(64)(65), a macromolecular crowding agent (53,66), or use of fused NC protein and added nucleic acid (67). In contrast, fast and efficient self-assembly of the CA lattice as a nanocoating on mica takes place even at CA concentrations <1 mM at close to physiological ionic strength and pH in the absence of crowding agents, NC and RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach developed in silico to model the consequences of phosphorylation at the level of a p24 hexamer has revealed that negative charges generated by phosphate conjugation at each serine position favors inter-monomer repulsion or cleavage of important inter-monomeric bonds required for preserving the stability of the hexameric ring of p24 [90] (Figure 3). According to these results, p24 phosphorylation may be considered as an event that could modify organization of p24 hexamers and at a higher order impact the organization of the viral core edifice.…”
Section: Protein Kinases Packaged Into Hiv-1mentioning
confidence: 99%
“…Changes observed in the internal diameter of the CTD of the non phosphorylated (left) and S 149 -phosphorylated CA hexamer (right) at 4500 ps. For clarity, only the CTD is represented in ribbons and one color is assigned per monomer [90]. …”
Section: Protein Kinases Packaged Into Hiv-1mentioning
confidence: 99%